Milhos com diferentes perfis nutricionais na alimentação de suínos da creche à terminação - Oliveira, Gisele Cristina de (2009)
Five experiments were carried out to determine the nutritional value and to verify the performance of pigs in the starting, growing and finishing phases fed with diets containing corns with different nutritional profiles. In the total digestibility trial (Exp. I) 14 crossbred barrow piglets, averaging 6.49 ± 0.16 kg initial live weight, allotted in a completely randomized design with seven treatments, six replicates repeated in time and one piglet per experimental unit were used. The values of digestible (DE) and metabolizable energy (ME), as fed basis for common corn (CC), extruded common corn (ECC), high-lysine corn (HLC), extruded high-lysine corn (EHLC), high-oil corn (HOC) and extruded high-oil corn (EHOC) were: 3,428 and 3,327 kcal / kg, 3,439 and 3,355 kcal / kg, 3,533 and 3,414 kcal / kg, 3,515 and 3,427 kcal / kg, 3,483 and 3,377 kcal / kg, 3,585 and 3,482 kcal / kg, respectively. In the performance experiment (Exp. II) 84 piglets, weaned at 21 days old, initial live weight from 6.06 ± 0.54 kg were used. The animals were allotted in a completely randomized design in a 3 x 2 factorial scheme, using three types of corn (CC, HLC and HOC), two forms of processing (processed or not by extrusion), seven replicates and two piglets per experimental unit. The treatments consisted of six diets: 1 - basal CC, 2 - basal ECC, 3 - basal HLC, 4 - basal EHLC, 5 - basal HOC and 6 - basal EHOC. The results indicated that there were no advantages in the digestibility and performance, by extruding corns with different nutritional profiles, for its use in commercial diets for piglets from 6 to 15 kg of live weight. In the total digestibility trial (Exp. III) 12 barrows were used (44.17 ± 0.84 kg initial live weight). The values of digestible energy (DE) as well as metabolizable energy (ME on an as-fed basis for CC, HLC and HOC, were: 3,396 and 3,275 kcal / kg, 3,248 and 3,139 kcal / kg, 3,445 and 3,308 kcal / kg, respectively. In order to determine the apparent and true ileal digestibility coefficients of amino acids, as well as the values of true digestible amino acids of the CC, HLC and HOC, an ileal digestibility test was done (Exp. IV) with T-canulated barrows ( "T" simple). The treatments consisted of three diets, with one of them as the sole source of protein (CC, HLC and HOC). In the performance experiment (Exp. V), 36 crossbred pigs (31.12 ± 4.07 kg initial live weight) allotted in a completely randomized design with three treatments, 12 replications and one pig per experimental unit were used. The treatments consisted of three diets: 1 - basal CC; 2 - basal HLC and 3 - basal HOC. It was observed no difference for the performance and carcass variables among corns with different nutritional profiles. The results of five experiments highlight the importance of segregating the corns in their real chemical and energetic composition as well as the values of true digestible amino acids for the formulation of pig diets in starting, growing and finishing phases.